2021
DOI: 10.1177/1038416220986887
|View full text |Cite
|
Sign up to set email alerts
|

Addressing employability challenges of business graduates in Bangladesh: Evidence from an emerging economy perspective

Abstract: This study aimed to explore and address the employability challenges of business graduates in the higher education sector in Bangladesh. Data were collected through semi-structured interviews and analysed applying thematic analysis (N = 35, 77% male, mean age = 34 years). Findings revealed that skill gaps, lack of quality education system, quality teachers, industry-university collaboration, backdated course curriculum, and corruption are important challenges for graduate employability in Bangladesh. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Tran 2012;Teng et al 2019;Virtanen and Tynjala 2019). Traditional teaching and learning often involves lectures, class discussions, memorisation, and regurgitation of theoretical course content during tests and examinations (Uddin 2021;Teng et al 2019). The focus is on the teacher and what they do (Mesny et al 2021).…”
Section: Business Schools Teaching and Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tran 2012;Teng et al 2019;Virtanen and Tynjala 2019). Traditional teaching and learning often involves lectures, class discussions, memorisation, and regurgitation of theoretical course content during tests and examinations (Uddin 2021;Teng et al 2019). The focus is on the teacher and what they do (Mesny et al 2021).…”
Section: Business Schools Teaching and Learning Methodsmentioning
confidence: 99%
“…As the environment within which companies operate change over time, so will their skill requirements. Fifth, some have argued that the discourse on graduate employability needs to be embedded within the context of the characteristics of the local labour market (Hossain et al 2020;Uddin 2021). Employability studies should, therefore, consider the contextual environment of the local labour market.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…They earn less due to not capitalizing on required time in business (Erogul & Na, 2021;Turnbull et al, 2020). The most significant constraints identified by the authors are (i) women are not allowed to go out for work due to cultural restrictions and (ii) lack of marketing facilities (Uddin, 2021;Echchabi et al, 2020). The significant barriers to the growth of SMEs are family decisions like the care of children and birth rates (Malinao, 2021;Hamid, 2020).…”
Section: Cultural Challengesmentioning
confidence: 99%
“…Women business graduates entrepreneurs are a vital factor from the economic point of view, not only for females but the overall economic condition of the countries of the South Asian region. The previous literature has proved that finance has been a global constraint for women entrepreneurs regardless of the country's economic position (Uddin, 2021;Tisdell et al, 2020;Echchabi et al, 2020;Erogul & Na, 2021). Previous literature confirmed that female entrepreneurs could not advertise their products; therefore, they are limited to a particular market around them (Islam et al, 2021;Kumar & Shukla, 2019).…”
Section: Hypothesized Direct Relationshipmentioning
confidence: 99%
“…A combination of these policy measures would allow for both a decrease in consumers’ welfare loss and a more competitive rice market in Bangladesh. Bangladesh is an emerging market economy, especially in South Asia (ADB, 2021; Suman et al., 2020; Uddin, 2021). The country is about to graduate from least developed to developing country (Chowdhury, 2020; Rahman, Sony, et al., 2020).…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%